Caracterização química e disponibilidade de enxofre em solos de várzea do Rio Grande do Sul. - Reis, Cecília Estima Sacramento dos (2008)
Soil chemical, physical and biological changes that occurr after soil flooding are very important for the irrigated rice crop, since they affect essential soil properties and nutrient availability. However, there is little information about the lowland soils in the State of Rio Grande do Sul, Brazil. The present study had as objective to evaluate the condition of 57 lowland soils regarding clay, organic matter and nitrogen content, ion exchange, acidity and phosphorus and sulphur availability, as well as to establish relationships among these soil attributes. Therefore, 57 samples of lowland soils were collected at a depth ranging from 0 to 20 cm (arable layer) in different locations, comprising the Santa Maria, Bagé, Hulha Negra, Jaguarão, Santa Vitória do Palmar, Camaquã, Uruguaiana, Barra do Quarai, Itaqui, São Borja, Eldorado do Sul, Rio Grande, São Lourenço do Sul and Pelotas Counties. Clay, total organic carbon and nitrogen, available phosphorus, potassium and sulphur, exchangeable calcium and magnesium, acidity, cation exchange ability and base saturation, were determined. In general, the studied lowland soils presented low organic matter, clay and nitrogen contents, a pH inferior to the recommended for the irrigated rice crop (5.5), low potential acidity, potassium levels bellow the limiting values, high calcium availability, magnesium, sulphur and phosphorus, besides the medium base saturation. Also, a high variability in the ion exchange ability and sulphur concentration available was found. The contents of total organic carbon, clay and nitrogen are highly correlated. The carbon content determined by elemental analysis and by the Walkley & Black method showed a high correlation. The relationships between the pH and the base saturation and between ion exchange ability and carbon content and clay are significant. Despite the low correlation between sulphur concentration available and organic carbon and clay contents, soils that show sulphur content below the critical level also possess low clay and organic carbon contents.